Sensitivity simulation of sea surface temperature variability in coastal waters off East Africa in relation to the Indian Ocean Dipole - Manyilizu, MC (African journal of marine science, 2023)
East African coastal waters in the tropical western Indian Ocean experience strong seasonality which varies yearly, leading to the establishment of a prominent interannual Indian Ocean Dipole (IOD). This has a significant influence on regional and global socio-economic, climatic and human development. Sea surface temperature (SST) variability in these waters and its association with ocean-atmosphere feedbacks and internal subsurface ocean dynamics in relation to the IOD is the subject of this study. The research used reference simulation accompanied with sensitivity simulations with forcings from higher frequency variabilities against climatological signals of ocean-atmosphere or internal subsurface ocean dynamics from 1980 to 2007. Wind forcing with higher-frequency variabilities was applied in all simulations. Cooling and warming during pure and positive IOD events leading El Niño events in the region is caused by a combination of both surface heat fluxes associated with ocean-atmosphere feedbacks, and internal subsurface ocean dynamics, from July and peaking in August and October, respectively. Such processes also dominate the warming (cooling) in the region during pure El Niño (La Niña) events from July to December (July to October) where the SST patterns extend southwards. The warmest (coolest) SST anomalies during positive (negative) IOD events co-occurring with El Niño (La Niña) events stay longer than other events, being characterised by bimodal peaking in August and December. Such SST patterns are significantly forced with ocean-atmosphere feedbacks that might be associated with Walker circulation driving links between the Indian and Pacific oceans; however, the peaking in August might be enhanced by small ocean dynamics off the Somali coast, probably owing to the existing upwelling systems during these conditions.